Diagnostic accuracy of refractometer and Brix refractometer to assess failure of passive transfer in calves: protocol for a systematic review and meta-analysis. (18th July 2016) - Buczinski, S.; Fecteau, G.; Chigerwe, M.; Vandeweerd, J. M.
Abstract: Calves are highly dependent of colostrum (and antibody) intake because they are born agammaglobulinemic. The transfer of passive immunity in calves can be assessed directly by dosing immunoglobulin G (IgG) or by refractometry or Brix refractometry. The latter are easier to perform routinely in the field. This paper presents a protocol for a systematic review meta-analysis to assess the diagnostic accuracy of refractometry or Brix refractometry versus dosage of IgG as a reference standard test. With this review protocol we aim to be able to report refractometer and Brix refractometer accuracy in terms of sensitivity and specificity as well as to quantify the impact of any study characteristic on test accuracy.